INCIDENCE OF THE COMMON GARDEN SNAIL, MACROCHLAMYS INDICABENSON, 1832 (GASTROPODA: ARIOPHANTIDAE) IN BANGALORE REGION - M. JAYASHANKAR,; M. S. REDDY,; S. RAMAKRISHNA, (The Bioscan, 2015)
Incidence of the common garden snail, Macrochlamys indica Benson, 1832 (Gastropoda: Ariophantidae) in different agri-horticultural ecosystems of Bangalore region is reported. Highest percentage of M. indica occurrence was in Bangalore North taluk (60%) and absent in Doddaballapur taluk (0%). The district wise distribution was found to be 22 (39%) villages in Bangalore urban district and 7 (12%) villages in Bangalore rural district. Co- occurrence of four different species of malacofauna viz., Cryptozona bistrialis, Mariella dussumeri(endemic) and Achatina fulica, Laevicaulis alte (invasive alien) with M. indica was assessed. M. indica - C. bistrialis combination co-occurred in 22 villages followed by M. indica - L. alte in 21, M. indica - A.fulica in 20 and M. indica-M. dussumeri in16 villages in Bangalore region. The findings are a first time prevalence records of the snail species in Bangalore region.